Upaya Guru dalam Mengenalkan Nilai-Nilai Agama Islam - Supriyani Supriyani; Mahrur Adam Maulana; Nihayatul Husna (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to describe: 1) Islamic religious education learning for tenth graders at Ma'arif 8 Vocational High School, Buayan District, Kebumen Regency, 2) Islamic religious education teachers' efforts in introducing Islamic religious values, and 3) inhibiting factors in introducing Islamic religious values. This study uses a qualitative method. The subjects of this study were Ma'arif 8 Vocational High School teachers, especially Islamic religious education teachers, principals, and students. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique used in this research is the data analysis technique of the Milles and Huberman model. There are three stages: data reduction, data presentation, and drawing conclusions. Based on the results of the study, the following conclusions can be drawn: Islamic religious education learning for tenth graders is carried out in three stages, namely introduction, core activity, and closing, the efforts of Islamic religious education teachers in introducing Islamic religious values, namely: introducing Islamic religious values ​​in the form of Islamic Aqidah, Islamic Shari'ah, and Islamic Morals that have been implemented but are still not optimal, as well as obstacles faced in introducing Islamic values, namely the background of students, social media, infrastructure, and promiscuity.